EXPERIMENTAL METHODOLOGY AIMED AT IMPROVING THE FRONT-LEG KICK SPEED IN KARATE - Radoslav Penov; Milen Chalakov (Journal of Applied Sports Sciences)
That article aims to present the development of an experimental methodology that improves the speed of kicks in Karate. The rationale behind creating the methodology is the fact that the speed of kicks in Karate is instrumental for overcoming the opponent. In addition, kicks are among the most commonly used techniques in matches. Therefore, our goal was to study the effect of applying the methodology we created onto improving the speed of kicks in Karate. In order to conduct the study, we used a video-computerized system to record and analyze the speed of kicks performed by the participants in the experiment. The results concerning the speeds of kicks were measured in identical ways in order to make sure that the survey was performed under uniform conditions. The input data was processed by means of kinematics analysis software. To prove the credibility of the data registered, we applied the necessary statistical analysis methods. We hope that by applying the methodology that we developed and have presented in this article, more coaches will start using modern tools and methods in order to improve the quality of the training process in Karate.